ANALISIS YURISPRUDENSI GUGATAN DAN PELANGGARAN HUKUM KERUSAKAN LINGKUNGAN OLEH KEGIATAN PERTAMBANGAN - Lumban Gaol, Chandra Erick Manaek Pandapotan; Isis Ikhwansyah; Nien Raples Siregar; Elisantris Gultom (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
Legal disputes concerning environmental damage from mining activities pose a crucial challenge to environmental law enforcement in Indonesia, often involving large corporations and government oversight bodies. A significant case involves LSM Lestari's lawsuit against PT Bukit Asam (PTBA) and the Ministry of Energy and Mineral Resources (Kemen ESDM) regarding coal mining impacts in Lahat, South Sumatra, culminating in Supreme Court Decision No. 5246 K/PDT/2024. This paper aims to analyze the Supreme Court's legal reasoning (ratio decidendi) in this decision, specifically examining its construction of PTBA's unlawful environmental acts, the legal basis for ordering environmental restoration and imposing penalty payments (dwangsom), and its determination of Kemen ESDM's supervisory role. The research employs a normative legal methodology, primarily using a case law analysis approach focused on the Supreme Court decision, supplemented by a statute approach reviewing relevant environmental and mining legislation. The findings reveal the Court affirmed PTBA committed unlawful acts violating the Civil Code and environmental laws (UU PPLH), mandating restoration and dwangsom accordingly. The ruling also obligated Kemen ESDM oversight, reinforcing governmental accountability. This decision strengthens environmental jurisprudence and NGO legal standing, despite potential enforcement challenges.